Tingkat Kecemasan Atlet Pencak Silat PSHT Wida Menghadapi Pertandingan Kota Wali Championship Tahun 2023 - Nur Mauliana Zekha, Novita; Amin, Nur; Aristiyanto, Aristiyanto; Nilawati, Ika (YLPK Mahardhika, 2023)
Pencak silat is a traditional martial art native to Indonesia. Achievement. PSHT Wida is one of the hermitages in Ungaran that educates beginner martial artists to become accomplished martial artists. An athlete's achievement requires physical, technical, and mental readiness. Anxiety is an unpleasant emotion, such as feeling uncomfortable, confused, anxious, and characterized by worry, disclosure, and fear which is sometimes experienced in different levels and situations. This research aims to determine the anxiety level of Pencak silat athletes at PSHT Wida in facing the 2023 Kota Wali Championship competition. This research method uses quantitative description with a cross-sectional design. Data collection used interviews and questionnaires to measure athletes' anxiety levels using the Sport Competition Anxiety Test (SCAT) anxiety instrument. The sample in this study was PSHT Wida athletes who took part in the Kota Wali Championship, totaling 15 athletes. The research results showed that the anxiety level of competition athletes in the low category was 6.7% (1 athlete), in the medium category 20% (3 athletes), and in the high category 73.3% (11 athletes). From the data results, it can be explained that the anxiety level of PSHT Wida athletes in competitions is in the high category.